Development of a Two-Tier Diagnostic Test to Assess Misconceptions about Biology Concepts at Primary School - Taşçi, Güntay (Science Insights Education Frontiers, 2024)
Developing tools to identify students’ misconceptions about basic biology concepts is necessary. Therefore, a two-tier diagnostic test was developed to determine such misconceptions in primary school (3rd-4th Grade) students. The test content includes two-tiered multiple-choice questions addressing common misconceptions found in the literature on biology subjects in science education at the primary school level. The test’s validation and reliability pieces of evidence are described through quantitative and qualitative data analysis of data obtained via the survey method. Data was collected from two samples in two stages, including 74 and 363 primary school students, respectively. The first stage has collected qualitative data by two-tier true-false items based on these common misconceptions. This data was analyzed per qualitative content analysis. Based on these findings, two-tier multiple-choice items were developed, and a two-tier diagnostic test was formed. In the second stage, data obtained was used to quantitative analyze the construct validity, internal consistency, and item parameters of the test. The study’s results provided evidence of the validity and reliability of the primary school biology misconceptions diagnostic test (PBMDT), which consists of eight two-tier multiple-choice items.